Clinical efficacy of β-lactam/β-lactamase inhibitor combinations for the treatment of bloodstream infection due to extended-spectrum β-lactamase-producing Enterobacteriaceae in haematological patients with neutropaenia: a study protocol for a retrospective observational study (BICAR). Issue 1 (23rd January 2017) - Gudiol, C; Royo-Cebrecos, C; Tebe, C; Abdala, E; Akova, M; Álvarez, R; Maestro-de la Calle, G; Cano, A; Cervera, C; Clemente, W T; Martín-Dávila, P; Freifeld, A; et al.
Abstract : Introduction: Bloodstream infection (BSI) due to extended-spectrum β-lactamase-producing Gram-negative bacilli (ESBL-GNB) is increasing at an alarming pace worldwide. Although β-lactam/β-lactamase inhibitor (BLBLI) combinations have been suggested as an alternative to carbapenems for the treatment of BSI due to these resistant organisms in the general population, their usefulness for the treatment of BSI due to ESBL-GNB in haematological patients with neutropaenia is yet to be elucidated. The aim of the BICAR study is to compare the efficacy of BLBLI combinations with that of carbapenems for the treatment of BSI due to an ESBL-GNB in this population. Methods and analysis: A multinational, multicentre, observational retrospective study. Episodes of BSI due to ESBL-GNB occurring in haematological patients and haematopoietic stem cell transplant recipients with neutropaenia from 1 January 2006 to 31 March 2015 will be analysed. The primary end point will be case-fatality rate within 30 days of onset of BSI. The secondary end points will be 7-day and 14-day case-fatality rates, microbiological failure, colonisation/infection by resistant bacteria, superinfection, intensive care unit admission and development of adverse events. Sample size: The number of expected episodes of BSI due to ESBL-GNB in the participant centres will be 260 with a ratio of control to experimental participants of 2. Ethics and dissemination: The protocol of the study was approved at the first site by the Research Ethics Committee (REC) of Hospital Universitari de Bellvitge. Approval will be also sought from all relevant RECs. Any formal presentation or publication of data from this study will be considered as a joint publication by the participating investigators and will follow the recommendations of the International Committee of Medical Journal Editors (ICMJE). The study has been endorsed by the European Study Group for Bloodstream Infection and Sepsis (ESGBIS) and the European Study Group for Infections in Compromised Hosts (ESGICH).